Retention time bracketing for targeted sphingolipidomics by liquid chromatography–tandem mass spectrometry. (21st January 2019) - Zhu, Lina; Zhou, Jieliang; Liang, Cui; Lee, Yie Hou
Aim: In complex biological matrixes, many sphingolipids are present with multiple reaction monitoring traces or lack of standard for verification, potentially leading to inaccurate identification and quantitation.Results/methodology: Based on these retention times of available standards, we devised a retention time bracketing approach to identify and predict sphingolipids of the same homologous series. Excellent concordance of predicted and observed retention times (<0.1 min) of sphingolipids were demonstrated. We also showed that many odd- and/or short-chain sphingolipids, commonly used as internal standards, are present in biological matrices including human serum, peritoneal fluid and cells.Conclusion: A retention time table, and a list of appropriate standards are presented, which are expected to be useful resources in targeted sphingolipidomics.